Factors That Affect Arab EFL Learners' English Pronunciation - Lardhi, Fatima Ali Salah; Noor Raha, Mohd Radzuan; Benraghda, Abdelmadjid (ESP World, 2017)
Majority of Arab EFL students reach the university with generally poor English and bad pronunciation in particular. Students in Arab countries have little opportunities to speak English where Arabic is their native language. Since correct pronunciation is very important to avoid misunderstanding when communicating with others and to build self-confidence when trying to speak in front of other people, the current paper investigates the reasons for Arab EFL students to face problems in English pronunciation. The participants were 10 Preparatory Intensive English (PIE) students of University Malaysia Pahang (UMP). Using an in-depth qualitative methodology which is individual interviews, all interviews were audio-recorded with the participants’ consent. The participants were undergraduate Arab EFL students who completed their high school and they do not have exposure to English language. All recorded interviews were analyzed manually. From the data analyzed some emergent themes were found. For instance, students confessed that the lack of using media such as listening to English songs and watching English news and movies affected their pronunciation competence. Furthermore, little emphasis on English pronunciation in formal classroom also contributes to students’ mispronunciation in English language. It was claimed that teachers do not correct students’ mispronunciation and there were no pronunciation activities conducted inside classrooms. Moreover, some social factors affect the students’ ability to speak in English with correct pronunciation, for instance, they speak English just inside the class during their lectures but whenever they leave their class, they use their own mother tongue. This paper attempts to shed some light on the impediments that Arab EFL students face in English pronunciation and to give recommendations on Pronunciation Language Strategies (PLS) that could be applied by the students to improve their English language pronunciation. Some other pedagogical recommendations are also included.